Individual performance and mobile banking: Role of task technology fit model - Mishra, Udgam (The Journal of Knowledge and Innovation, 2023)
The study examines how task technology fit factors determine the individual performance of mobile banking application users. There isn’t any study about individual performance in the context of mobile banking using the task technology fit model in Nepal, thus it will be a novel study from a Nepalese perspective. The study investigates the factors of the task technology fit model and collects 181 data using a google survey questionnaire. Data were then analyzed using structural equation modeling by AMOS. The findings indicate that task characteristics have a positive and significant effect on task technology fit and the use of mobile banking has a positive and most promising effect on individual performance. However, a positive but insignificant impact can be seen of technology characteristics on task technology fit and task technology fit on the use of mobile banking. This study provides insight into the financial institutions in Nepal regarding the perception of their users toward mobile banking application services.